Molecular characterization of protease inhibitors from the Hessian fly, [Mayetiola destructor (Say)] - Maddur, Appajaiah Ashoka (Kansas State University, 2005)
Analysis of transcriptomes from salivary glands and midgut of the Hessian fly [Mayetiola destructor (Say)] identified a diverse set of cDNAs that were categorized into five groups, group I – V, based on their phylogenetic relationship. All five of these groups may encode putative protease inhibitors based on structural similarity with known proteins. The sequences of these putative proteins among different groups are highly diversified. However, sequence identity and structural analysis of the proteins revealed that all of them contained high cysteine residues that were completely conserved at their respective positions among these otherwise diversified proteins. Analysis of bacterial artificial chromosome (BAC) DNA for two groups, group I (11A6) and group II (14A4), indicated that group I might be a single copy gene or genes with low copy number whereas group II exists as multiple copies clustered within the Hessian fly genome. To test the inhibitory activity and specificity of these putative proteins, recombinant proteins were generated. Enzymatic analysis of the recombinant proteins against commercial and insect gut proteases demonstrated that recombinant proteins indeed are strong inhibitors of proteases with different specificities. Northern analysis of the representative members of five groups revealed that the group I-IV genes were expressed exclusively in the larval stage with variations among groups at different larval stages. The group V (11C4) genes were expressed in the late larval and pupal stage. Tissue specific gene expression analysis revealed that group I-IV genes were predominantly expressed in malpighian tubules whereas the group V genes were abundantly expressed in the salivary glands. Localization experiments with the antibody for representative members from group II (14A4) demonstrated that the protein was predominantly localized in the malpighian tubules and in low amounts in the midgut, suggesting that malpighian tubules are the primary tissue of 14A4 inhibitor synthesis. The overall results indicated that the Hessian fly contains a complex network of genes that code for protease inhibitors which regulate protease activities through different developmental stages of the insect.
Keywords: Protease inhibitors; Proteolysis; cDNA library; Proteases; Inhibition; Gene expression; Salivary glands; Hessian fly; Biology, Entomology (0353); Biology, Genetics (0369); Biology, Molecular (0307)